MULTI-SENSORY ACTIVITY IN EARLY CHILDHOOD EDUCATION: TEACHERS’ PERCEPTION ON THE IMPORTANCE OF ACTIVITY IMPLEMENTATION - Syazwani Aniyah Manja; Abdul Halim Masnan; Mazlina Che Mustafa; Norazilawati Abdullah (Jurnal Penyelidikan Sains Sosial, 2022)
The purpose of this study was to survey teachers’ perceptions on the importance ofimplementing multi-sensory activities to children. Perception among early childhood educationteachers is seen based on teachers’ general perceptions on the importance of multi-sensoryactivities in early childhood education and teachers’ reaction toward the importance ofimplementation according to the type of multi-sensory activities. This study is a survey studyusing a questionnaire by Goodwin (2008) about Sensory Experiences in the Early ChildhoodClassroom: Teachers’ Use of Activities, Perceptions of the Importance of Activities, andBarriers to Implementation. Thus the respondents involved in this study are teachers of earlychildhood education in Proton City Area, Muallim District, Perak. The researcher chooses touse purposeful sampling and the total number of respondents involved is 30 teachers. Thefindings of the study found that a total number of 27 respondents is (90%) agreed on theimportance of multi-sensory activities in early childhood education. The highest score ofpercentages for teachers’ perceptions toward the importance of implementation according tothe type of multi-sensory activities, a total of 26 participants (86.7%) agreed with visual stimuliactivity and art materials and activities implementation. Meanwhile the lowest score is containof 21 participant (70%) that agreed with the implementation of multi-sensory activities throughOutdoor Play. Although there are high and low percentage scores but it is still seen asimportant in the implementation of multi-sensory activity in early childhood education.